Managerial Skills and Success of Small-Scale Entrepreneurs in Kampala Uganda - Kibuuka, Muhammad (Canadian International Journal of Social Science and Education, 2015)
A multi-sector coverage of small-scale enterprises was explored in this study to address these research objectives: (1) extent to which managerial skills were possessed; (2) extent to which small-scale entrepreneurs were successful; (3) differences in extent of managerial skills and success among small-scale entrepreneurs; and (4) relationship between managerial skills and success. Employed as strategies to elicit the data were the descriptive comparative, descriptive correlation and ex-post facto designs; administration of validated and tested for reliability researcher devised questionnaires; frequencies, means, t-test, One Way ANOVA and regression analysis. The findings showed moderate extent of managerial skills in terms of conceptual, human and technical skills; less successful internally and more successful externally; the extent of managerial skills and success differed significantly according to gender, education level, business form and years in business; the extent of managerial skills possessed was positively and significantly correlated with all aspects of internal and external success; conceptual and technical skills significantly depicted small-scale entrepreneurs’ success. Thus, technical and conceptual skills needed to be more promoted through entrepreneurial and business skills in universities; education of small-scale entrepreneurs on formation of joint ventures and ongoing training programs for skills formation and development.
Keywords: Managerial skills; Small scale entrepreneurs; Success